Frequency, Risk Factors, and Prognosis of Dehydration in Acute Stroke - Cortés-Vicente, Elena; Guisado-Alonso, Daniel; Delgado-Mederos, Raquel; Camps-Renom, Pol; Prats-Sánchez, Luis; Martínez-Domeño, Alejandro; Martí-Fàbregas, Joan (Frontiers in Neurology, 2019)
Objective: To determine the frequency, risk factors, and impact on the outcome of dehydration after stroke. Methods: In this cross-sectional observational study, we included prospectively and consecutively patients with ischemic and hemorrhagic stroke. The serum Urea/Creatinine ratio (U/C) was calculated at admission and 3 days after the stroke. Dehydration was defined as U/C>80. Patients were treated in accordance with the standard local hydration protocol. Demographic and clinical data were collected. Neurological severity was evaluated at admission according to the NIHSS score; functional outcome was assessed with the modified Rankin scale score (mRS) at discharge and 3 months after the stroke. Unfavorable outcome was defined as mRS > 2. Results: We evaluated 203 patients; 78.8% presented an ischemic stroke and 21.2% a hemorrhagic stroke. The mean age was 73.4 years ±12.9; 51.7% were men. Dehydration was detected in 18 patients (8.9%), nine patients at admission (4.5%), and nine patients (4.5%) at 3 days after the stroke. Female sex (OR 3.62, 95%CI 1.13–11.58, p = 0.03) and older age (OR 1.05, 95%CI 1–1.11, p = 0.048) were associated with a higher risk of dehydration. Dehydration was significantly associated with an unfavorable outcome at discharge (OR 5.16, 95%CI 1.45–18.25, p = 0.011), but the association was not significant at 3 months (OR 2.95, 95%CI 0.83–10.48, p = 0.095). Conclusion: Dehydration is a treatable risk factor of a poor functional outcome after stroke that is present in 9% of patients. Females and elders present a higher risk of dehydration.